ANALISIS KOMPETENSI SUMBER DAYA MANUSIA APARATUR DALAM KEBIJAKAN INVESTASI DAERAH (Studi Kasus pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Provinsi Nusa Tenggara Barat) - Mohamad Imran (Universitas Mataram, 2026)
This study examines the competence of civil-service human resources at the Office of Investment and One-Stop Integrated Services of West Nusa Tenggara Province in implementing regional investment policy. It focuses on the competence profile of public officials, the barriers to capacity development, and the strengthening strategies required for modern investment services. The research employed a descriptive qualitative approach. Data were collected through in-depth interviews, non-participant observation, and document review of regulations, performance reports, staffing data, and investment realization records. Informants were selected purposively and through snowball sampling, including structural officials, functional officers, cross-sector staff, academics, and business actors. Data were analyzed using the interactive model of Miles, Huberman, and Saldana. The findings show that officials’ competence is fairly good, especially in integrity, discipline, and service ethics. However, gaps remain in OSS-RBA mastery, understanding investment regulations, promotional capability, and investment-control analysis. The main barriers include competence disparities, a limited number of functional personnel, constrained human resource development budgets, suboptimal digital infrastructure, and weak interagency coordination. The study recommends competency-based training, stronger digital literacy, merit-based talent management, knowledge-management systems, and multi-stakeholder collaboration forums.